SAN PHRANET MUNICIPALITY COMMUNICATION STRATEGY FOR COMMUNITY DEVELOPMENT ENGAGEMENT OF THE PEOPLE SAN PHRANET, SAN SAI, CHIANG MAI - Songsawangphaiboon, Sang (Academic Journal Phranakhon Rajabhat University, 2025)
The environment context of San Phranet Subdistrict is a semi-urban, semi-rural area with a diverse mix of ethnicities, age groups, educational levels, and economic backgrounds. Technology, especially new media, plays a significant role in influencing how information disseminated by the San Phranet Subdistrict Municipality is received by the public The objectives of this research are 1) to study the environmental context affecting the communication of San Phranet Subdistrict Municipality, San Sai District, Chiang Mai Province, and 2) to study the communication strategies and patterns of San Phranet Subdistrict Municipality, San Sai District, Chiang Mai Province, using qualitative research methods including in-depth interviews with a target group of 31 individuals responsible for communication strategies, budgeting, and public relations of San Phranet Subdistrict Municipality, as well as representatives of information recipients residing in the subdistrict. The research employed purposive sampling. The findings of the research are as follows: Environmental factors affecting communication to information recipients include geographical and demographic conditions, socio-cultural conditions of indigenous and migrant communities allocated in housing development and the economic conditions and occupations of the population. Communication strategies and patterns of San Phranet Subdistrict Municipality align with policies, projects, and activities of the municipality, utilizing communication channels such as traditional media through thought leaders and contemporary media including the press, applications, and municipal executives and staff. Attention and collaboration among stakeholders are required to maximize communication efficiency, ensuring equal access for all groups of information recipients, disseminating useful information, and fostering community participation in collaborative community development. The environmental context of the area, along with the diversity in ethnic groups, gender, age, occupation, education level, and access to technology, significantly impacts public information awareness among residents of San Phranet Subdistrict.